Digital storytelling as a motivating tool for promoting children's literature to the grade1 students of Tandang Sora Elementary School - Abao, Nonalu Sareena A.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Storytelling is a big part of a person's childhood and everyone has their own share of childhood stories. The stories may be from original books bought from bookstores or given by relatives. There are also stories which were created from a parent or guardian's imagination. Storytelling, like childhood, has also developed from traditional to digital. In line with this, the study focused on digital storytelling format and its use as a motivating tool for promoting children's literature.
A total of 40 grade 1 students, age 6 to 8, from Tandang Sora Elementary School were asked to participate on the digital storytelling activities. Two digital stories with different themes were used, while a comprehension test and story preference test were given after the activity. Also, the section's adviser and the teacher-librarian who mans the library were interviewed.
The results of the comprehension test and the data gathered from the story preference test revealed that: a) the level of comprehension of the students can be considered average; b) digital storytelling are successful in getting the attention, interest, desire, and action of the respondents; and c) the students prefer stories with people as main characters.
Digital storytelling is proved to be useful in motivating children respondents in using literature and using the library. Children can have fun and be entertained, while learning moral lessons and enhancing their vocabulary and listening skills through watching and listening to a story. The activity only needs to be properly managed, so that the disadvantages mentioned by the teachers will lessen.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Tandang Sora Elementary School; Digital storytelling -- Philippines -- Quezon City; School children -- Philippines -- Quezon City